The Role of Dual Earner Families in Children's Psychological Well-Being: Literature Review - Miftahul Huda; Elok Halimatus Sa’diyah (DIROSAT: Journal of Education, Social Sciences & Humanities, 2024)
Economic demands often encourage husbands and wives in a family to work, and this has impacts that include both positive and negative sides. The positive impact is especially visible in the family economic aspect, where family income can be increased. However, the negative impact is more pronounced in the psychological aspect of the family, especially on the psychological well-being of children. This study is an analysis of the literature that seeks to investigate how children's psychological well-being is affected in the context of dual-earner families. Search engines are used as a tool to search for and collect relevant data. As a result, 12 studies were found which were then used as data sources. These studies show that dual-earner families tend to have a negative impact on children's psychological well-being, such as poor mood swings, higher levels of depression, increased levels of anxiety, increased anger, aggressive behavior, negative attitudes towards school, and a number of other negative behaviors. It is hoped that the results of this literature study can become the basis for further empirical research, especially in the Indonesian context, which may have differences in findings compared to previous studies